NOVEL APPROACHES TO NON-INVASIVE BLOOD GLUCOSE MEASUREMENT - Kh. A. Kurdanov; A. D. Elbaev; A. D. Elbaeva; R. I. Elbaeva (Кардиоваскулярная терапия и профилактика, 2017)
Aim. Development of a novel method for non-invasive blood glucose measurement based on the hemodynamics parameters, and implementation of non-invasive glucometer.Material and methods. Totally, 170 persons studied, of the age 20-75 y.o.: with arterial hypertension (n=70), diabetes type 2 (n=70), healthy (n=30). Blood pressure (BP) was measured on both arms of patient, fasting and after a meal. The mean values of systolic BP, diastolic BP, pulse BP were calculated, and BP coefficient as their relation. At the same time chemistry was done for glucose levels.Results. The case was being resolved by the method of mathematical modelling using Statistica software. Correlational and functional multifactorial tests were done, in all groups. The highest correlational coefficients in all dimensions represent the relations of glucose level with BP response (0,75-0,85), which was selected for regression equations for BP and glucose relation. Optimal regression equations were used for the device measuring glycemia non-invasively.Conclusion. A novel method for non-invasive glycemia diagnostics is developed, based on the modelling of correlation of systemic hemodynamics and blood glucose concentration. The relations obtained, are used for invention of automatic non-invasive glucometer by the pulse wave parameters. Novelty has been proved by RF patents: “Method for non-invasive glucose concentration measurement in blood”; “Equipment for non-invasive assessment of blood glucose concentration”. Non-invasive glucometer can be used in healthcare institutions and for individual use.